2009
DOI: 10.1111/j.1365-2435.2008.01508.x
|View full text |Cite
|
Sign up to set email alerts
|

No allelopathic effect of the dominant forest‐floor lichen Cladonia stellaris on pine seedlings

Abstract: Summary 1.The lichen Cladonia stellaris forms dense mats and dominates the forest-floor vegetation in latesuccessional oligotrophic boreal forests. This lichen is rich in polyphenolic secondary compounds, and through allelochemical effects of these compounds the dense mat formed by C . stellaris is assumed to have negative effect on forest regeneration and soil microbial functioning. 2. We examined the effect of C . stellaris and its secondary metabolite usnic acid on nutrient uptake and growth of pine ( Pinus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 55 publications
(89 reference statements)
0
22
0
Order By: Relevance
“…It has been recognized for a long time that nutrient dissolution from the plant substrate provides mineral nutrition to epiphytic lichen communities (Des Abbayes 1951;Nash 2008), but the inhibition of lichens by bark compounds has also recently been claimed (Koopmann et al 2007). Several in vitro studies suggest that competitive relationships between terricolous lichens and plants depend on allelopathic interferences (Lawrey 1984(Lawrey , 1986(Lawrey , 2009), but recent ecological investigations do not support this finding (Kyto¨viita and Stark 2009). …”
Section: Introductionmentioning
confidence: 90%
“…It has been recognized for a long time that nutrient dissolution from the plant substrate provides mineral nutrition to epiphytic lichen communities (Des Abbayes 1951;Nash 2008), but the inhibition of lichens by bark compounds has also recently been claimed (Koopmann et al 2007). Several in vitro studies suggest that competitive relationships between terricolous lichens and plants depend on allelopathic interferences (Lawrey 1984(Lawrey , 1986(Lawrey , 2009), but recent ecological investigations do not support this finding (Kyto¨viita and Stark 2009). …”
Section: Introductionmentioning
confidence: 90%
“…Brown and Mikola (1974) showed that lichens have negative allelopathic effects on mycorrhizas and tree seedlings. In contrast, recent studies have revealed that the effects of lichens are either neutral or even beneficial (Stejlen et al 1995;Kytöviita and Stark 2009). However, the interplay between reindeer grazing and vegetation might create complex interactions that in turn have various effects on the establishment, initial growth, and survival of pine seedlings (Väre et al 1996;Jonsson 1999).…”
Section: Introductionmentioning
confidence: 99%
“…This is because the concentrations of largely hydrophobic allelochemicals leaching into mineral soils from lichen mats rarely reach toxic (or even detectable) levels (Kershaw 1985, Stark et al 2007, Kytoviita and Stark 2009. Studies have shown the removal of lichen mats to be more detrimental to tree growth than their presence (Bonan and Shugart 1989, Lawrey 1995, Crittenden 2000.…”
Section: Allelopathymentioning
confidence: 99%
“…Kershaw (1985) explored many of the microclimatic influences of lichen mats, and concluded that lichen mats generally decreased temperature fluctuation and rates of evaporation at the soil surface, as compared to non-vegetated surfaces. This soil-climate buffering may favour the gradual development of moss or vascular plant components of the system, and has been suggested as the mechanism responsible for increased growth of mycorrhizae and their associated trees in boreal forests (Bonan 1990, Crittenden 2000, Stark et al 2007, Kytoviita and Stark 2009. Similarly, feathermosses act as a moisture-regulating buffer between the atmosphere and soil, and in doing so may facilitate the dominance of spruce canopies over pine in later stages of forest development in some systems.…”
Section: Facilitationmentioning
confidence: 99%
See 1 more Smart Citation